Distribution and sources of macrolitter on the seafloor in Belgian fisheries areas - Vanavermaete, David; Verlé, Katrien; Devriese, Lisa I.; De Cauwer, Karien; De Schrijver, Coline; Torreele, Els; Vandecasteele, Loes; Velimirovic, Milica; Tirez, Kristof; Hostens, Kris; De Witte, Bavo (Frontiers in Marine Science, 2023)
Marine litter is recognised as a global environmental concern. Seafloor litter can provide important information to help assess the status of the marine ecosystem and is relatively easy to collect on a regular basis. The Belgian fisheries area covers different parts of the OSPAR Greater North Sea region and the Celtic Seas. In these regions, seafloor litter data was gathered by quantifying the litter items caught in the trawl net during two different fisheries surveys to investigate litter distribution on both regional and local scales. In the international beam trawl survey (BTS), covering essentially the OSPAR Greater North Sea and Celtic Seas, an average of 2.2 ± 0.05 items.ha−1 were caught with a median of 1.4 items.ha−1. In the environmental monitoring survey (EMS) only the Belgian part of the North Sea (BPNS) was covered and a smaller cod-end mesh size was used, resulting in 12.7 ± 1.7 litter items.ha−1 in the coastal zone (< 12 nm) and 2.8 ± 0.2 items.ha−1 in the more offshore zone (> 12 nm). In both surveys plastic items were predominant, representing up to 88% of the collected litter in the BPNS. The impact of human activities at sea such as fisheries, sand extraction, wind farms and dredge disposal was investigated. A low but significant correlation (up to r2 = 0.48) was found between fishing activities and the amount of litter registered in the BPNS, but not for the OSPAR Greater North Sea and Celtic Seas.